2021
DOI: 10.21203/rs.3.rs-451236/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indigofera Tinctoria Leaf Powder As A Promising Additive To Improve Indigo Fermentation Prepared With Sukumo (Composted Polygonum Tinctorium Leaves)

Abstract: Being insoluble in the oxidize form, indigo dye must be solubilized by reduction for it to penetrate textile. One of the procedures is the reduction by natural bacterial fermentation. Sukumo, composted leaves of Polygonum tinctorium, is a natural source of indigo in Japan. Although sukumo has an intrinsic bacterial seed, the onset of indigo reduction with this material may vary greatly. Certain additives improve indigo fermentation. Here, we studied the effects of Indigofera tinctoria leaf powder (LP) on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…LP acts to accelerate indigo reduction in the natural fermentation of D- sukumo , which produces slow change in microbiota during fermentation ( Lopes et al, 2021a ). In this study, we aim to confirm the accelerative effect of LP on microbiota using T- sukumo , which without LP would produce rapid change in microbiota, and D- sukumo , which without LP would produce slow change in microbiota.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LP acts to accelerate indigo reduction in the natural fermentation of D- sukumo , which produces slow change in microbiota during fermentation ( Lopes et al, 2021a ). In this study, we aim to confirm the accelerative effect of LP on microbiota using T- sukumo , which without LP would produce rapid change in microbiota, and D- sukumo , which without LP would produce slow change in microbiota.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that a stable state under alkaline anaerobic conditions, that induced dominance of the obligate anaerobe Proteinivoraceae was an important factor for maintaining of indigo fermentation for long period ( Tu et al, 2019b ). However, even in anaerobic conditions dominated by family Proteinivoraceae , which is equivalent to genus Alkalicella , at the beginning of the fermentation, indigo reduction was not initiated ( Lopes et al, 2021a ). In the present study, we confirm the more specific prerequisite phase transition of microbiota that is required for indigo reduction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations